Vertical distributions of Zn, Cd, Pb, and Cu at tropical coastal sediments: in case of west coast of Peninsular Malaysia - Lasumin, Nazerita; Mohamed, Khairul Nizam; Mohamat Yusuff, Ferdius @ Ferdaus (Oriental Scientific Publishing Company, Inc., 2022)
The level and pollution status of Zn, Cd, Pb, Cu in sediment cores of Bagan Pasir estuary, Sungai Buloh estuary, and the coastline of Port Dickson was assessed. Based on the vertical profiles of metals concentrations, the order of metals’ concentration in decreasing manner was Zn>Pb>Cu>Cd at Bagan Pasir and Sungai Buloh stations, while Zn>Cu>Pb>Cd at Port Dickson station. Most of the analyzed metals were below the Interim Sediment Quality Guidelines and the effect range-low (ERL) at all sampling stations. The results of geo-accumulation index, contamination factor and pollution load index classified the sediments quality as unpolluted with studied metals with the exception of the element Pb at certain depths of the sediment cores as well as historical pollution at bottom sediment at Sungai Buloh station. Therefore, metal concentrations in the sediments of these stations were not at an alarming stage, however, requires regular monitoring from the authorities to maintain sustainable management of these areas especially at Sungai Buloh due to anthropogenic activities.